AN ANALYSIS OF MORAL VALUE IN STATING THE PRINCIPLE IN “KICKBOXER” MOVIE - Bejo Sutrisno; Albert Situmorang (STIBA IEC JAKARTA, 2021)
The aims or this research are to analyze the moral values ​​and principles of moral values that are delivered in the